A study of the therapeutic effects of yoga on symptoms associated with ADHD in children: Systematic review and meta-analysis - Mu, Xintong; Luo, Yang; Jia, HaiChang; Li, Xinjia; Huang, Jing (Quality in Sport, 2025)
Background: Attention-deficit/hyperactivity disorder (ADHD) is a chronic developmental disorder with a high prevalence in children and the long-term nature of treatment. Although the use of yoga as a non-pharmacologic treatment is increasing in the ADHD population, the conclusion of its effectiveness in treating symptoms in children with ADHD remains to be explored. Objective: The primary goal of this meta-analysis was to systematically summarize and analyze the efficiency of yoga in treating symptoms such as attention problems, emotional problems, and behavioral control in children with ADHD, as well as to serve as a guide for further studies and therapeutic procedures in the management of ADHD in children. Materials and methods: This study was conducted using the Cochrane Handbook and the PRISMA Guidelines Statement for Systematic Reviews. A total of five databases, PubMed, Embase, Cochrane, Web of Science, and Ovid, were searched up to December 2024. Excel was utilized for data extraction, and Review Manager was used for data processing, analysis, and literature quality evaluation. Results: In all, nine publications were enrolled in the study, and 285 participants—142 in the experimental group and 143 in the control group—met the inclusion requirements. The intervention lasted between 2 and 20 weeks, and all study participants were between the ages of 3 and 15. The outcome metrics consisted of measures of five ADHD-related symptoms: inattention, sustained attention, hyperactivity/impulsivity, emotional instability, and anxiety. Conclusion: The intervention of yoga had an ameliorative effect on several symptoms of inattention, sustained attention, emotional instability, and hyperactivity/impulsivity in children with ADHD, but not statistically significant on anxiety symptoms.